A Novel Rat Model for Comprehensive Microvascular Training of End-to-End, End-to-Side, and Side-to-Side Anastomoses - Yin, Xiaoliang; Ye, Gengfan; Lu, Jun; Wang, Lijun; Qi, Peng; Wang, Haifeng; Wang, Junjie; Hu, Shen; Yang, Ximeng; Chen, Kunpeng; Wang, Daming (Journal of Reconstructive Microsurgery, 2019)
Background End-to-end, end-to-side, and side-to-side microvascular anastomoses are the main types of vascular bypass grafting used in microsurgery and neurosurgery. Currently, there has been no animal model available for practicing all three anastomoses in one operation. The aim of this study was to develop a novel animal model that utilizes the rat abdominal aorta (AA), common iliac arteries (CIAs), and the median sacral artery (MSA) for practicing these three types of anastomosis.Methods Eight adult Sprague–Dawley rats were anesthetized and then laparotomized. The AA, MSA, and bilateral CIAs were exposed and separated from the surrounding tissues. The length and diameter of each artery were measured. The relatively long segment of the AA without major branches was selected to perform end-to-end anastomosis. One side of the CIAs (or AA) and MSA were used for end-to-side anastomosis. The bilateral CIAs were applied to a side-to-side and another end-to-side anastomosis.Results Anatomical dissection of the AA, CIAs, and MSA was successfully performed on eight Sprague–Dawley rats; four arterial-to-arterial anastomoses were possible for each animal. The AA trunk between the left renal artery and right iliolumbar arteries was 15.60 ± 0.76 mm in length, 1.59 ± 0.15 mm in diameter, for an end-to-end anastomosis. The left CIA was 1.06 ± 0.08 mm in diameter, for an end-to-side anastomosis with the right CIA. The MSA was 0.78 ± 0.07 mm in diameter, for another end-to-side anastomosis with the right CIA or AA. After finishing end-to-side anastomosis in the proximal part of bilateral CIAs, the distal portion was juxtaposed for an average length of 5.6 ± 0.25 mm, for a side-to-side anastomosis.Conclusion This model can comprehensively and effectively simulate anastomosis used in revascularization procedures and can provide more opportunities for surgical education, which may lead to more routine use in microvascular anastomosis training.
Keywords: bypass; anastomosis training; animal model